Overview of the Waste Management System at Kariango Market, Mattiro Bulu District, Pinrang Regency - Aswani, Irma; Nadirah, Nadirah; Ridwan, Ridwan; Muslimin, Muslimin; Wijayanti, Eva (Journal of Community Health Provision, 2024)
Waste is the result of human activities and comes from a natural process, where waste often causes problems, especially in public places. The market is an important means of trade for the community so that it has the potential to produce quite a lot of waste. The market is a certain place, where sellers and buyers meet, including facilities where sellers can display their merchandise by paying a fee, (Environmental Health Requirements TTU, Ministry of Health of the Republic of Indonesia 1993). The research method used is observational with a descriptive approach. Sampling by Randong Sampling, where the sample size obtained was 211 people / traders, the collection was carried out with an observation sheet in the form of a checklist. The results of the observation showed that out of 211 traders, only 2 traders (0.9%) had good category trash containers and 209 traders (99.1%) had sufficient category trash containers, this shows that the existence of good trash containers in Kariango Market is still lacking. The results of data collection in the field, the collection system showed that out of 211 traders (100%) the collection of trash was in a good category. Garbage transportation can be seen that from 211 traders who were sampled, 208 traders (98.6%) transportation is categorized as good and 3 traders (1.4%) transportation is categorized as sufficient. For traders who do not have good garbage containers, they should immediately have good containers and what must be considered is that the material of the garbage container must be strong enough, waterproof, easy to fill, empty and easy to clean. The Department of Cleanliness, Parks and Fire of Pinrang Regency in order to maximize the transportation process should carry out transportation twice a week, namely after every market day.